1979
DOI: 10.1088/0031-9155/24/3/013
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical determination of scatter factors at depths in walls of cylindrical chambers

Abstract: A theoretical evaluation has been made of the contribution from scattered photons to dose at depths in the walls of cylindrical cavity chambers for photon beams in the energy range 2-30 MV. Scatter factors calculated for graphite, Perspex and water walls over a range of depths and thicknesses show satisfactory agreement with the experimental results of other workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…A theoretical study (McEwan 1979) in satisfactory agreement with the experimental results of Barnard eta1 (1964) has shown that f ( t ) may be expressed as f ( t ) = at -bt2, for low atomic number materials and for the ranges of t of interest in this work. Integration of equation ( 1) with this form of f ( t ) gives where ( ) is the cavity gas dose per unit energy fluence.…”
Section: Cavity Ionisationsupporting
confidence: 86%
See 3 more Smart Citations
“…A theoretical study (McEwan 1979) in satisfactory agreement with the experimental results of Barnard eta1 (1964) has shown that f ( t ) may be expressed as f ( t ) = at -bt2, for low atomic number materials and for the ranges of t of interest in this work. Integration of equation ( 1) with this form of f ( t ) gives where ( ) is the cavity gas dose per unit energy fluence.…”
Section: Cavity Ionisationsupporting
confidence: 86%
“…where rw is the radius of the cavity, f ( r w ) is the scatter factor for a point at the centre of a water cylinder of radius rw (McEwan 1979), and the term [ 1, is evaluated for the spectrum at the measurement depth. Then also…”
Section: Absorbed Dose Measurement In Watermentioning
confidence: 99%
See 2 more Smart Citations
“…They found T,, = 1.005 + 0.002 for a 20 MeV x-ray beam. McEwan (1979) calculated T, for the same type of chamber and found T2(] = 1.002, consistent with the experimental results. Since these values are uncertain but close to unity, we have ignored the effect of the build-up cap on calculated values of F,, although it may have a +0.2-+0.50/0 effect.…”
Section: The Fa Factorsupporting
confidence: 82%